End-use energy analysis in the Malaysian industrial sector - Saidur, Rahman; Rahim, N.A.; Masjuki, Haji Hassan; Mekhilef, Saad; Hew, Wooi Ping; Jamaluddin, M.F. (Elsevier, 2009)
The industrial sector is the second largest consumer of energy in Malaysia. In this energy audit, the most important parameters that have been collected are as follows: power rating and operation time of energy-consuming equipments/machineries; fossil fuel and other sources of energy use; production figure; peak and off-peak tariff usage behavior and power factor. These data were then analyzed to investigate the breakdown of end-use equipments/machineries energy use, the peak and off-peak usage behavior, power factor trend and specific energy use. The results of the energy audit showed that the highest electrical energy-using equipment was an electric motor followed by pumps and air compressors. The specific energy use has been estimated and compared with four Indonesian industries and it was found that three Malaysian industries were more efficient than the Indonesian counterpart. The study also found that about 64 electrical energy was used in peak hours by the industries and the average power factor ranged from 0.88 to 0.92. The study also estimated energy and bill savings using highly efficient electrical motors along with the payback period.